Vegetable Gardening and Marketing in Kirtipur Area of Kathmandu - Rai, Dhyanendra Bahadur (Nepalese Journal of Development and Rural Studies, 2017)
Vegetable gardening is one of the important branches of vegetable farming in which vegetables are produced for the purpose of self-consumption and local market. In these days, the demand of fresh vegetable is increasing day by day because of rapid population growth, urbanization and growing awareness towards green vegetable in the kitchen. Hence, in the urban fringes, vegetable gardening has appeared as one of the productive enterprises for cash generation as well as self-employment. This study is completely based on primary data collected in the field by household questionnaire survey, key informants interview as well as focus group discussion (FGD). Finding clearly indicates that the cultivation of vegetable around Kirtipur area is gradually increasing and also able to fulfill few demands of vegetables in the local market of Kirtipur. This area has emerged as one of the vegetable growing pocket area among the outlying areas of Kirtipur Municipality. Nepalese Journal of Development and Rural StudiesVol. 14 (Joint issue) (1&2), 2017, Page: 28-35